Patterns of Ethylene and Carbon Dioxide Evolution during Cotton Explant Abscission - Marynick, Marilyn C. (1977)
The relationship between abscission and the evolution of ethylene and CO(2) was examined in explants and explant segments of cotton seedlings (Gossypium hirsutum L. cv. Acala SJ-1) under both static and flow system conditions, and in the presence and absence of mercuric perchlorate. Explant excision was immediately followed by increased ethylene evolution (wound ethylene); senescence was also accompanied by increased ethylene evolution (senescence ethylene). One or two ethylene peaks were found to interrupt the low background rate of ethylene evolution during the period between excision and senescence. The first intermediate ethylene peak coincided with a rise in CO(2) evolution; however, precedence could not be established. No statistical correlations were discovered between either intermediate ethylene peak and abscission. The best statistical correlation was found between wound ethylene and abscission at 12 hr after excision. No positive correlations were found between senescence ethylene and abscission. Implications of these results for the understanding of the role of ethylene in explant abscission are discussed. Relationships between a number of different explant treatments and ethylene evolution were also examined. Ethylene production in response to indoleacetic acid applications, abscisic acid applications, and different types of wounding is summarized. It was concluded that the results of the standard abscission bioassay (conducted in Petri dishes) have not been influenced by unnatural ethylene accumulations.